ANALYSIS OF THE INFLUENCES OF DIVIDEND PAYOUT RATIO, RETURN ON EQUITY, GROWTH AND FIRM SIZE ON STOCK VALUE WITH LEVERAGE AS MEDIATING VARIABLE - Novia Utami (Jurnal Akademi Akuntansi, 2020)
This study aims to examine the internal factors that influence the value of a company's shares mediated by the leverage. The sample of this research is the firms listed in the Indonesia Stock Exchange (IDX) during the period 2017 - 2019. Data collected with the purposive method and obtained 102 companies in the year observed. This study uses multiple regression analysis and regression analysis with interaction. Based on the results of multiple regression analyses, this study found that return on equity and total assets influence the value of shares with positive direction, while debt to equity, dividend payout ratio and growth sales do not affect share value. While based on the results regression analysis with interactions, this study found that leverage strengthens the effect of dividend payout ratio and sales growth on share value, and weaken the impact of return on equity and total assets on share value.